Problematika Moral Generasi Milenial dalam Perspektif Bimbingan dan Konseling Islami - Randi Saputra; Nanda Alfan Kurniawan (Universitas PGRI SUMATERA BARAT, 2023)
The development of the world of information technology has an impact on the moral condition of the millennial generation. Millennials are individuals who are in the age range of 18-25 years. The ease of accessing technological devices ultimately causes a sense of caring and tolerance among individuals to decrease. Moral is a collection of care, tolerance and responsibility that supports individuals to be able to adapt to various conditions of change that occur. Moral is one of the targets of Islamic guidance and counseling services in the personal and social fields, as well as the main component of character building for the millennial generation. This study aims to provide an analysis of the problematic condition of moral aspects experienced by the millennial generation in the perspective of Islamic guidance and counseling. This study uses a descriptive approach with a literature study method. The data of this study used articles from research results in the last two years. The results of the literature review show that the moral problems experienced by the millennial generation can becaused by internal and external factors. Keywords: morals, millennial generation, islamic guidance and counseling.